Effects of scientific policies in the Spanish university : research projects in English language and Linguistics = Repercusión de la política científica en la Universidad Española ; proyectos de investigación en Lengua y Lingüística Inglesa - Fernández Bajón, María Teresa; Pérez Ruiz, Leonor (2008)
We briefly explore the relationships between scientific and educational policies and the Spanish university system, and try to identify some converging themes in these fields and some future directions for the improvement of the scientific research done at tertiary level. This article also offers a general view of the different funded research projects in English language and linguistics carried out by Spanish university groups with the aim of reporting on the trends and interests.
Pretendemos explorar de forma breve las relaciones entre las políticas científicas y las educativas enel sistema universitario español, y a su vez intentar identificar algunos temas concluyentes y futuras direcciones para la mejora de la investigación llevada a cabo en la universidad. También daremos un repaso general a distintos proyectos de investigación financiados que se llevan a cabo por grupos de investigación en universidades españolas en lengua y lingüística inglesas con el fin de señalar las tendencias e intereses de los investigadores.
En Revista Actualidades Investigativas en Educación, vol. 8, no. 1 (enero-abril 2008)
Descripción basada en el contenido visto el 18 de diciembre, 2024